2009
DOI: 10.1080/02699050902970737
|View full text |Cite
|
Sign up to set email alerts
|

How many people return to work after acquired brain injury?: A systematic review

Abstract: About 40% of the people with traumatic or non-traumatic ABI are able to return to work after 1 or 2 years. Among those with acquired traumatic brain injury a substantial proportion of the subjects were either not able to return to their former work or unable to return permanently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
148
1
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(185 citation statements)
references
References 60 publications
12
148
1
17
Order By: Relevance
“…Coetzar et al [12] reported that individuals with moderate to severe TBI showed a significant change in their work status post-injury when compared to that of pre-injury. Among TBI survivors, the unemployment rate was reported to be substantially high [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Coetzar et al [12] reported that individuals with moderate to severe TBI showed a significant change in their work status post-injury when compared to that of pre-injury. Among TBI survivors, the unemployment rate was reported to be substantially high [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Further work in this area may play an important role in clarifying the potential of laboratory training procedures for improving real-life functional outcomes in individuals with brain dysfunction. In addition, as a large proportion of individuals with brain injury are unable to maintain long-term employment following their injury (van Velzen et al, 2009), one important goal for future research is to develop training interventions that are capable of improving return to work and other real-life outcomes in individuals with brain injury.…”
Section: Driscoll Et Almentioning
confidence: 99%
“…Several recent studies have been published providing systematic reviews of the post-TBI return to work literature [6][7][8]. Saltychev et al [6] reviewed 80 studies published in English from 1990 through 2011.…”
Section: Introductionmentioning
confidence: 99%